Wheelchair Servicing for Older Adults: Cross-Sectional Study - Anand Mhatre; Abigail Dumm; Muyun Zhao; Lorena Parra Rodriguez (JMIR Rehabilitation and Assistive Technologies)
Abstract BackgroundWheelchairs are assistive mobility devices known to experience frequent part failures and breakdowns within 6 months of regular use. No tools or technologies exist to monitor the wheelchairs’ condition or usage and inform stakeholders and users regarding when or how often they need to undergo servicing to avoid critical part failure. ObjectiveWe aimed to test the association between wheelchair usage and manual wheelchair damage, part failures, and consequences for older wheelchair users and evaluate their preferences for a new wheelchair servicing technology. MethodsA cross-sectional study was performed with older manual wheelchair users atInstituto Nacional de Geriatría in Mexico. Demographic data, wheelchair information, failure counts, and preferences for new technology (sensor and smartphone app for servicing) were collected using surveys. Road shocks experienced by the wheelchair were collected for a week using a sensor. ResultsTen participants (mean [SD] age, 78.8 [11.8] y; 8 female and 2 male) participated. Seven experienced an average (SD) of 2.86 (1.36) self-reported part failures. Road shocks correlated with self-reported loose brake failures (r(8)P,r(8)P=r(8)P.r(9)P. ConclusionsIn this study, the association between wheelchair usage and failures showed that data-driven wheelchair inspection schedules should be determined through a collaborative approach involving researchers and stakeholders in wheelchair repair provision and older adult users. Older adults are interested in using new technology to engage in wheelchair servicing.